Improvement of Energy Network by Naturally Farming of Chlorophyll-bearing Algae: Effects of Culture Condition Changes for the Yield of Microalgae - Kobayashi Naoto (International Journal of Limnology, 2019)
In this study, basic cultivation experiments were performed on microalgae Desmodesmus sp, then, the experiment results were deductively expanded, and the use of paddy in the off-season for farmers is advocated. As a result of the continuous culture experiments using 100 mL test tubes, 101.3 mg dry biomass was harvested in the aeration culture using the BG-11 medium. In the aeration culture with mixing CO2, the maximum harvest was obtained under the 10%-CO2 concentration. Considering about CO2 concentration, the condition of 1%-CO2 was superior in CO2 use efficiency. Based on the changes in the pH of the medium, algae such as Desmodesmus sp exchanges ions between the inside of the cell and the surrounding environment, and changes the surrounding environment in order to adapt themselves. In the proforma calculation of second crops in paddy fields, 26.4 million tons dry biomass is harvested in 120 days long of culture a year. Considering that the harvested dry biomass amount, 187 × 106 GJ power energy is obtained by burning them. This amount of energy corresponds to about 5.2% of total electricity.
Keywords: Microalgae